Programmable Prpg With Test Compression Capabilities - Purnima Pandey, Sanjeeva Reddy Peddapalli (International Journal of Advanced Science and Technology, 2020)
This project describes a low-power (LP) programmable generator capable of producing pseudorandom test patterns with desired toggling levels and enhanced fault coverage gradient compared with the best-to-date built-in self-test (BIST)- based pseudorandom test pattern generators. It is comprised of a linear finite state machine (a linear feedback shift register or a ring generator) driving an appropriate phase shifter, and it comes with a number of features allowing this device to produce binary sequences with preselected toggling (PRESTO) activity. We introduce a method to automatically select several controls of the generator offering easy and precise tuning. The same technique is subsequently employed to deterministically guide the generator toward test sequences with improved fault-coverage-to pattern-count ratios. Furthermore, this proposes an LP test compression method that allows shaping the test power envelope in a fully predictable, accurate, and flexible fashion by adapting the PRESTO based logic BIST (LBIST) infrastructure. The proposed architecture is extended in such that the patterns generated from PRPG is gone through CUT and then to TRA to perform ATE.